1990
DOI: 10.1159/000185971
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Prospective Study on Renal Effects of Two Different Contrast Media in Humans: Protective Role of a Calcium Channel Blocker

Abstract: Contrast media affect renal hemodynamics. Hyperosmolality is regarded as the major factor responsible for renal hemodynamic changes. In this study, the role of osmolality was evaluated in 30 hospitalized patients without risk factors during intravenous pyelography. Contrast media with low and high osmolality were used. In addition, nifedipine was administered before infusion of high-osmolality contrast to evaluate the role of calcium ions in radiocontrast-induced changes of renal hemodynamics. Hyperosmolar con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 17 publications
2
42
1
1
Order By: Relevance
“…We, like many investigators before [13,[19][20][21][22][23][24][25][26] , identified a decrease in renal blood flow and an increase in renal vascular resistance (decreased conductance) in the first 60 min after radiocontrast injection. In addition, like other investigators, we found a return of renal blood flow to baseline within 120 min of injection [22] . Thus, our findings are entirely consistent with several previous short-term observations.…”
Section: Discussionsupporting
confidence: 53%
“…We, like many investigators before [13,[19][20][21][22][23][24][25][26] , identified a decrease in renal blood flow and an increase in renal vascular resistance (decreased conductance) in the first 60 min after radiocontrast injection. In addition, like other investigators, we found a return of renal blood flow to baseline within 120 min of injection [22] . Thus, our findings are entirely consistent with several previous short-term observations.…”
Section: Discussionsupporting
confidence: 53%
“…Patients (n=20) who received sublingual nifedipine did not have a significant increase in serum creatinine, while those in the placebo group did (Rodicio et al, 1990). In another study, patients (n=30) who received nifedipine had an increase in renal plasma flow following administration of contrast, while patients in the placebo group had a decrease in renal flow (Russo et al, 1990). One other study showed that nitrendipine use cause a significant reduction in the GFR in the placebo group compared to little or no change in GFR in the nitrendipine group (Neumayer et al, 1989).…”
Section: Calcium Channel Blockersmentioning
confidence: 98%
“…There are other medicines that may attenuate the risk of CIN. Calcium-channel blocking medications attenuate both the magnitude and duration of renal vasoconstriction after contrast medium administration (Russo et al, 1990). In patients with type 2 diabetes mellitus and hypertension and/or angina requiring calcium-channel blocking medications, these medications should be continued if contrast medium administration is planned.…”
Section: Prevention Strategies To Attenuate Contrast-induced Nephropamentioning
confidence: 99%